2022
DOI: 10.3390/risks10090170
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Financial Footnotes, Audit Fees, and Risk Management Committee

Abstract: We find that the readability of financial footnotes and risk management committees contributes to audit fees. We use observations from 758 companies listed in Indonesia for 2014–2018, and moderated regression analysis is used for statistical analysis. The results show that the readability of financial footnotes will affect audit fees paid, and RMC strengthens the relationship between the readability of financial footnotes and audit fees. In addition, we also used robustness assays to address endogeneity issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
1
0
0
Order By: Relevance
“…The view that independent directors are associated with improved corporate reporting readability agreed with that of Harjoto et al (2020) in the USA. Elbadry et al (2015) and Harjoto et al (2020) agreed with the findings of Prabhawa and Harymawan (2022) in Indonesia during 2014 to 2018 and studied 758 companies and found that independent directorships in firms significantly enhanced the relationship between readability of financial statements as measured by FOG index and audit fees.…”
Section: Empirical Literature Reviewsupporting
confidence: 84%
“…The view that independent directors are associated with improved corporate reporting readability agreed with that of Harjoto et al (2020) in the USA. Elbadry et al (2015) and Harjoto et al (2020) agreed with the findings of Prabhawa and Harymawan (2022) in Indonesia during 2014 to 2018 and studied 758 companies and found that independent directorships in firms significantly enhanced the relationship between readability of financial statements as measured by FOG index and audit fees.…”
Section: Empirical Literature Reviewsupporting
confidence: 84%
“…It also supports their differences in interests (Prabhawa and Harymawan 2022). The agents are responsible for any tasks or decisions that occur within the company on behalf of the principals (Prabhawa and Harymawan 2022). The principal sometimes has goals and interests that differ from those of the agents (Prabhawa and Harymawan 2022;Pratama et al 2022).…”
Section: Agency Costs Complexity Of the Annual Report And Firm Profit...mentioning
confidence: 97%
“…It discusses the relationship between shareholders, as principals, and managers, as agents (Pratama et al 2022;Tarjo 2022). It also supports their differences in interests (Prabhawa and Harymawan 2022). The agents are responsible for any tasks or decisions that occur within the company on behalf of the principals (Prabhawa and Harymawan 2022).…”
Section: Agency Costs Complexity Of the Annual Report And Firm Profit...mentioning
confidence: 97%
See 2 more Smart Citations